Evaluation of Bone Mineral Densitometry Measurements in Newly Diagnosed Acromegaly Patients - Murat Çalapkulu; Muhammed Erkam Sencar; İlknur Öztürk Ünsal; Davut Sakız; Hayri Bostan; Hakan Düğer; Mustafa Özbek; Erman Çakal (Türk Osteoporoz Dergisi)

(untitled)
Objective:Acromegaly is a chronic disease that causes high concentrations of growth hormone (GH) and insulin-like growth factor-1 (IGF-1). GH and IGF-1 levels have important effects on bone homeostasis, bone turnover, and bone remodeling. The results of studies investigating the relationship between acromegaly and bone mineral density (BMD) are controversial. The aim of the current study was to evaluate BMD in newly diagnosed acromegaly patients and to determine the relationship between GH and IGF-1 levels with BMD.Materials and Methods:This cross-sectional study was conducted on 36 newly diagnosed acromegaly patients without a history of hypogonadism, whose BMD values can be obtained from the records of University of Health Sciences Turkey, Dışkapı Yıldırım Beyazıt Training and Research Hospital. The relationship between GH and IGF-1 levels and BMD measured from the femur and lumbar regions was examined separately.Results:The mean age of the patients was 46.2±12.5 years. Median IGF-1 and BH levels were 551 ng/mL and 8.2 ng/mL, respectively. While 58.3% of the patients had osteopenia, no osteoporosis was found in any patient. A positive correlation was found between the BMD value measured from the femoral neck and IGF-1 (r=0.484, p=0.036) and GH (r=0.595, p=0.007) levels. There was no significant correlation between BMD measurements evaluated from lumbar vertebrae and GH and IGF-1 levels.Conclusion:It was found that the increase in GH and IGF-1 levels in newly diagnosed eugonadal acromegaly patients increased BMD measured from the femur. There was no significant relationship between BMD measured from the lumbar region and GH and IGF-1 levels.